Alexithymia and aggression in adolescents: their gender differences - Carrasco-Muñoz, Miguel Alfredo (2021)
Objective. To know the differences in alexithymia and aggression between male and female adolescents in the fourth and fifth year of high school education. Methods. Level of descriptive-comparative research, type of basic research, transversal design. We worked with a sample of 374 high school students, considering the non-probabilistic sampling of census type that selected 173 men and with probabilistic sampling of stratified type were considered 201 women. The Toronto Alexithymia Scale (T.A.S.-20) and the Buss Perry Aggression Questionnaire were used as instruments for data collection. Likewise, the difference in proportions was used for data analysis. Results. When comparing the differences with alexithymia, according to the gender of the students, a P value = 0.530 was obtained, this being greater than 0.05; so the null hypothesis is accepted and it is stated that there are no significant differences in alexithymia between male and female adolescents. On the other hand, when comparing the differences with respect to aggression according to gender, a P value = 0.001 was obtained, this being less than 0.05; therefore, the null hypothesis of equality is rejected and it is affirmed that there are differences in aggression between male and female adolescents. Conclusions. There is a relationship between alexithymia and aggression in male and female adolescents.